Comic-Based Module Development Andro-Web to Improve Problem Solving Ability in Physics in High School Students - Suci Arin Annisa; Albertus Djoko Lesmono; Y Yushardi (Universitas Lambung Mangkurat, 2020)
This research aims to determine the validity of comic-based module andro-web on the subject of an ideal gas and increased capacity problem-solving physics students after using comic-based module andro-web on the subject an ideal gas. The research uses the design nieveen model of development. In the assessment phase, the module then tried out on 30 grade XI science 2 Jenggawah Senior High School. The instruments of product quality are an instrument validation and instrument increased capacity problem solving of physics students about pre-test and post-test completed by using 5 indicators problem-solving. The average score validation comic-based module andro-web by validator 81,7 % with valid category. The score validation by user validator obtained score 93,3 % with a very valid category. Besides, increased capacity problem-solving physics students a score was obtained for 47,3 % in by test n-gain medium category. Thus, it was stated that comic-based module andro-web can be used in teaching material XI science class and will raise the ability problem-solving physics students on the subject of an ideal gas.